Salt mobilization and transport in an upland desert catchment of the Lower Arkansas River Basin of Colorado - Zimmer, Carly Elizabeth, author; Bailey, Ryan, advisor; Niemann, Jeffrey, committee member; Kampf, Stephanie, committee member (Colorado State University. Libraries, 2021)
Salt loading can significantly alter water quality in large river basins. Salt deposits occur naturally and anthropogenically and are transported to water bodies through overland flow and other environmental factors. The mobilization and transport of salt in high-desert regions can hinder the sustainability of crop production in downstream irrigated regions. Salinity transport and loading has been extensively investigated in regions of irrigation. However, little research has been conducted regarding salt mobilization in analogous regions with high-desert characteristics and little cultivation. The goal of this thesis is to understand the mobilization of salt in predominantly undeveloped, uncultivated upland catchments in a semi-arid climate with sparse vegetation cover and steep gradients. The thesis is composed of two primary objectives. 1) Quantify the salt load contribution from the Purgatoire River Watershed, a high-desert watershed, to the Arkansas River, and 2) Identify possible major environmental factors that control the mobilization of salts in natural upland catchments. A variety of field and computational methods were used to complete these two objectives. Electrical conductivity (EC) data loggers were placed at two locations along the Purgatoire River to quantify in-stream salt ion (SO4, Ca, Na, Mg, HCO3, K, Cl) loading. Daily in-stream loading (kg/day) of each salt ion was estimated using laboratory results of a set of water samples (n = 10) at these sites and stochastic linear regression techniques. Results indicate that the overall mass loading of salt exported by the Purgatoire River to the Arkansas River, and the ratio of salt in the Arkansas River to the Purgatoire River, is significantly affected by annual rainfall. In 1990 (490 mm), the Purgatoire River exported approximately 64,600,000 kg of salt to the Arkansas River, accounting for 21.7% of the salt in the Arkansas River after merging. In 2020 (262 mm), the volume of annual precipitation fell by 47% and the Purgatoire River exported approximately 18,000,000 kg of salt, 72% less than 1990, to the Arkansas River accounting for 11.2% of the salt in the Arkansas River after merging. Results indicate that upstream desert catchments can have a large effect on salinity loads in irrigated river valleys such as the Arkansas River Valley. For objective 2, environmental factors investigated for salt mobilization control include precipitation depths, land use type, topographic slope, percent calcium carbonate (CaCO3) in soil, and percent calcium sulfate (CaSO4) in soil. These factors were used to compute a spatial varying salt mobilization index throughout the Purgatoire River Watershed. The resulting index map shows hot spots of potential salt mobilization, which can be verified through additional research. Similar maps can be made for other high-desert regions to investigate potential sites of salt mobilization.
Keywords: mobilization and transport; semi-arid; water quality; salinity; Lower Arkansas River Basin; upland catchment